Evaluasi Tepung Kedele Terproteksi Tanin Kondensasi dari Ekstrak Daun Sengon (Albizia falcataria) terhadap Ketahanan Degradasi oleh Mikroba di Rumen - Ratu Putri Ganesa; Afzalani Afzalani; Fadillah Hermiseptia; Raguati Raguati; Fachroerrozi Hoesni (Universitas Batanghari Jambi, 2023)
Soybean meal (SBM) is a quality feed with high protein and organic matter content but is easy to degrade by microbes in the rumen. A high degradation rate in the rumen causes potential protein loss as ammonia and energy in the form of fermentation heat, CO2 gas, and methane gas. This study aimed to determine the effect of SBM protected with condensed tannins (TK) from sengon leaves on its fermentability by rumen microbes. This study used a completely randomized design (CRD) consisting of four treatments and five replications. Treatments were of P1 = SBM unprotected with condensed tannin (CT) (control); P2 = SBM- protected 2% CT; P3 = SBM-protected 4% CT, and P4 = SBM- protected 6% CT. The amount of CT (0, 2, 4, 6%) was calculated and converted to the amount of sengon leaves equivalent to 0, 226.24, 452.49, and 678.72 g/kg SBM based on CT content in sengon leaves of 8.84%. SBM samples were weighed as much as 0.5 g, then put into a serum bottle with a capacity of 100 ml, added 40 ml of a mixture of rumen fluid and McDougall's buffer (1:4 v/v), closed with a rubber stopper, climb sealed using an aluminum seal, and incubated in an incubator for 3, 6, 9, 12, 24, and 48 hours. The variable measured was in vitro cumulative gas production (GP), methane production (CH4), dry matter degradation (DMD), organic matter degradation (OMD), metabolism energy (ME), and production of microbial protein (PMP). The results showed that the treatment of SBM protected with condensed tannins from sengon leaf extract had a significant effect (P<0.05) on reducing GP, CH4, DMD, OMD, ME, and PMP. The Treatment of P1 (control) was higher produced of GP, CH4, DMD, OMD, ME, and PMP (P<0.05) compared to P2, P3, and P4. But between P2, P3, and P4 were not significantly different (P>0.05). This study concluded that the use of condensed tannin at levelof 2% could be used to protect soybean meal from microbial degradation in the rumen.